Biodiversity: Living Wealth of Nepal - Malla, U. M (Himalayan Review, 2011)
Available with fulltext. Key words: Geography; Environment; Biodiversity The Himalayan Review Nepal Geographical Society Vol. XXXII 2001 Page: 1-24 Uploaded date: 7 June, 2011